(untitled) (Culturas Científicas, 2021)
In economics, research is divided into two major methodologies: theoretical-mathematical models and empirical studies. By studying theoretical models and empirical methods (exemplified by Randomized Controlled Trials (i.e. RCT)) we show the limitations of both methods, concluding that neither of these can develop explanations of how things actually happen, but only how possibly happen, since both need an interpretative link that allows extrapolation from their own system (i.e. the one of the model and the one of the empirical study, respectively) to a target system. Models have a general domain and can account for mechanisms. On the other hand, RCTs are internally valid and connected to the real world, but with a very specific domain. Although neither can answer broad questions about a phenomenon of interest, they can complement each other in order to generate more reliable extrapolations about a target system. Nevertheless, this can only be done if the mechanisms and the context in which an evidence occurs are well known.